Acute Visual Loss and Mesenteric Nodules: Two Case Reports of Atypical Presentations of Calciphylaxis - Wu Tzen Lim; Rajiv Juneja; Rachel Yi Ping Tan (Case Reports in Nephrology and Dialysis)
Introduction: Calciphylaxis is a systemic disease that predominantly affects individuals with chronic kidney disease, particularly in the advanced stages. It is a potentially life-threatening condition with significant morbidity. The exact underlying mechanisms leading to calciphylaxis are not fully understood. Cutaneous manifestations are the typical presentation of calciphylaxis, where patients develop painful skin ulcers affecting their extremities. However, calciphylaxis involving visceral organs are rare. Case Presentations: We present 2 cases where the initial clinical picture of calciphylaxis was atypical. The first case is a haemodialysis patient presenting with unilateral acute vision loss, mimicking giant cell arteritis. The second case is a failed transplant graft recipient on peritoneal dialysis with incidental radiological findings of heavily calcified mesenteric nodules. Conclusion: These cases highlight the importance of a high clinical suspicion of calciphylaxis as it can masquerade other clinical conditions.